Historical epidemiology of hepatitis C virus (HCV) in select countries – volume 3. (December 2015) - Liakina, V.; Hamid, S.; Tanaka, J.; Olafsson, S.; Sharara, A. I.; Alavian, S. M.; Gheorghe, L.; El Hassan, E. S.; Abaalkhail, F.; Abbas, Z.; Abdou, A.; Abourached, A.; et al.
Summary: Detailed, country‐specific epidemiological data are needed to characterize the burden of chronic hepatitis C virus (HCV) infection around the world. With new treatment options available, policy makers and public health officials must reconsider national strategies for infection control. In this study of 15 countries, published and unpublished data on HCV prevalence, viraemia, genotype, age and gender distribution, liver transplants and diagnosis and treatment rates were gathered from the literature and validated by expert consensus in each country. Viraemic prevalence in this study ranged from 0.2% in Iran and Lebanon to 4.2% in Pakistan. The largest viraemic populations were in Pakistan (7 001 000 cases) and Indonesia (3 187 000 cases). Injection drug use (IDU) and a historically unsafe blood supply were major risk factors in most countries. Diagnosis, treatment and liver transplant rates varied widely between countries. However, comparison across countries was difficult as the number of cases changes over time. Access to reliable data on measures such as these is critical for the development of future strategies to manage the disease burden.